ANALISIS MINAT BELI KONSUMEN PADA RESTORAN BENGKEL PERUT BUDE DI BANDAR LAMPUNG - Sri Suyarti; Yuan Rizki Hidayat (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
Many restaurants with many service concepts or ideas are offered to attract customerenthusiasm. Restaurants which have old stand up as well as restaurant which is just opened try torecognize or offer new menus so that it can be accepted better by all buyer or consumer. That conditionwill cause the competition between restaurant which progressively tightens to attract many buyers sothat they come to visit and enjoy what have been provided.From the result of data analysis and hypothesis testing about influence of service to consumerenthusiasm at Bengkel Perut “BUDE” Restaurant Bandar Lampung is obtained the conclusion that thereis Influence of service to consumer enthusiasm at Bengkel Perut “BUDE” Restaurant.